Human Antibody Responses Following Vaccinia Immunization Using Protein Microarrays and Correlation With Cell-Mediated Immunity and Antibody-Dependent Cellular Cytotoxicity Responses - Frey, Sharon E; Stapleton, Jack T; Ballas, Zuhair K; Rasmussen, Wendy L; Kaufman, Thomas M; Blevins, Tammy P; Jensen, Travis L; Davies, D Huw; Tary-Lehmann, Magdalena; Chaplin, Paul; Hill, Heather; Goll, Johannes B (The Journal of infectious diseases, 2021)
There are limited data regarding immunological correlates of protection for the modified vaccinia Ankara (MVA) smallpox vaccine. A total of 523 vaccinia-naive subjects were randomized to receive 2 vaccine doses, as lyophilized MVA given subcutaneously, liquid MVA given subcutaneously (liquid-SC group), or liquid MVA given intradermally (liquid-ID group) 28 days apart. For a subset of subjects, antibody-dependent cellular cytotoxicity (ADCC), interferon-γ release enzyme-linked immunospot (ELISPOT), and protein microarray antibody-binding assays were conducted. Protein microarray responses were assessed for correlations with plaque reduction neutralization titer (PRNT), enzyme-linked immunosorbent assay, ADCC, and ELISPOT results. MVA elicited significant microarray antibody responses to 15 of 224 antigens, mostly virion membrane proteins, at day 28 or 42, particularly WR113/D8L and WR101H3L. In the liquid-SC group, responses to 9 antigens, including WR113/D8L and WR101/H3L, correlated with PRNT results. Three were correlated in the liquid-ID group. No significant correlations were observed with ELISPOT responses. In the liquid-ID group, WR052/F13L, a membrane glycoprotein, correlated with ADCC responses. MVA elicited antibodies to 15 vaccinia strain antigens representing virion membrane. Antibody responses to 2 proteins strongly increased and significantly correlated with increases in PRNT. Responses to these proteins are potential correlates of protection and may serve as immunogens for future vaccine development. NCT00914732.